IMPACT OF THE TABLE HEIGHT AND THE OPERATOR'S HEIGHT ON THE LEVEL OF RADIATION DELIVERED TO INTERVENTIONAL CARDIOLOGISTS. Issue 1 (21st May 2019) - Faroux, Laurent; Blanpain, Thierry; Fernandez, Anthony; Nazeyrollas, Pierre; Tassan-Mangina, Sophie; Heroguelle, Virginie; Tourneux, Christophe; Metz, Damien
ABSTRACT: Interventional cardiologists count among the health professionals that are most exposed to ionising radiation. To minimise exposure, it is recommended that the patient be placed at the maximum distance possible from the X-ray source, but this recommendation has not been clinically validated. We aimed to investigate the impact of the average table height on the level of radiation delivered to cardiologists performing coronary interventions. The population for analysis included all invasive coronary procedures performed in our centre from March to June 2017. The primary endpoint was operator radiation exposure, as assessed using personal electronic dosimeters located on the operator's left arm. In total, 225 invasive coronary procedures were analysed. When the average table height was 1126 mm or more, the operators received a radiation dose that was, on average, 53% lower than when the table was lower than 1126 mm. This reduction remained significant by multivariate analysis adjusted for the operator.